The Role of Parents in the Development of Adolescents' Self-esteem at SMA Negeri 1 Kuta Utara - Rani Swari, Ni Kadek Puspita; Kamajaya, Gede; Tamin, Imron Hadi (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
This research aims to analyze the role of parents in the development of adolescents' self esteem at SMA Negeri 1 Kuta Utara. Self-esteem is a vital component in the formation of adolescent identity, shaped by interactions and socialization patterns within the family environment, particularly through the parenting styles adopted. George Herbert Mead explains that the development of self-esteem is closely linked to the formation of the self-concept, which consists of two primary components: the “I” and the “Me.” In the context of adolescence, self esteem evolves through social interaction, wherein individuals learn to recognize themselves based on the social responses they receive and reflect upon. The theoretical framework employed in this study is George Herbert Mead’s theory of socialization. The findings of this research indicate that parents play a central role in fostering adolescents’ self-esteem a role that encompasses parenting methods and the socialization patterns practiced within the family setting. Keyword: parental role; self-esteem; adolescents; parenting style